2010
DOI: 10.1111/j.1365-3040.2009.02064.x
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and coordination of root growth at low water potentials: recent advances from transcriptomic and proteomic analyses

Abstract: Progress in understanding root growth regulation and adaptation under water-stressed conditions is reviewed, with emphasis on recent advances from transcriptomic and proteomic analyses of maize and soybean primary roots. In both systems, kinematic characterization of the spatial patterns of cell expansion within the root elongation zone showed that at low water potentials, elongation rates are preferentially maintained towards the root apex but are progressively inhibited at more basal locations resulting in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
136
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(147 citation statements)
references
References 85 publications
7
136
0
4
Order By: Relevance
“…In agreement, previous research using maize root has found that water stress enhances proline content through the up-regulation of pyrroline-5-carboxylate synthetase [71]. In addition, increased carbohydrate metabolism may accelerate the synthesis of some amino acids through glycolysis and the tricarboxylic acid cycle [71,72]. Accumulation of amino acids, together with other osmotic regulators, including soluble sugars and ions, decreases the osmotic potential and enhances the capacity for water absorption under drought conditions [70,73].…”
Section: Effects Of Drought-induced Stress On Rice Leavessupporting
confidence: 70%
“…In agreement, previous research using maize root has found that water stress enhances proline content through the up-regulation of pyrroline-5-carboxylate synthetase [71]. In addition, increased carbohydrate metabolism may accelerate the synthesis of some amino acids through glycolysis and the tricarboxylic acid cycle [71,72]. Accumulation of amino acids, together with other osmotic regulators, including soluble sugars and ions, decreases the osmotic potential and enhances the capacity for water absorption under drought conditions [70,73].…”
Section: Effects Of Drought-induced Stress On Rice Leavessupporting
confidence: 70%
“…If macropores exist, preferential root growth occurs resulting in a clustered root system (Logsdon & Allmaras, 1991;Tardieu, 1994). Root growth can be restricted due to increase in penetration resistance, which primarily results from increase in tension in water film between the soil particles on drying (Whalley et al, 2005;Whitmore & Whalley, 2009;Whalley et al, 2005;Mckenzie et al, 2009;White & Kirkgaard, 2010;Yamaguchi & Sharp, 2010). The data presented in the literature on root distribution as affected by NT and CT are not consistent.…”
mentioning
confidence: 72%
“…Pro contributes to osmotic adjustment by protecting cellular turgor. Consequently, water influx into cells is enabled by a more negative water potential compared with the outside medium (for review, see Yamaguchi and Sharp, 2010). In contrast to these physiological processes, little is known about the metabolic and molecular networks involved in drought adjustment (Spollen et al, 2008;Krasensky and Jonak, 2012).…”
mentioning
confidence: 99%
“…The maintenance of root growth is mediated by the plant hormone abscisic acid. Abscisic acid prevents excessive ethylene production and growth inhibition by promoting the transport of Pro to the root apex (for review, see Yamaguchi and Sharp, 2010). Pro contributes to osmotic adjustment by protecting cellular turgor.…”
mentioning
confidence: 99%